2021
DOI: 10.3389/fpsyt.2021.607612
|View full text |Cite|
|
Sign up to set email alerts
|

Risk Perception and PTSD Symptoms of Medical Staff Combating Against COVID-19: A PLS Structural Equation Model

Abstract: Medical staff were battling against coronavirus disease 2019 (COVID-19) at the expense of their physical and mental health, particularly at risk for posttraumatic stress disorder (PTSD). In this case, intervening PTSD of medical staff and preparing them for future outbreaks are important. Previous studies showed that perceived stress was related to the development of PTSD. Hence, in this study, the association between risk perception of medical staff and PTSD symptoms in COVID-19 and the potential links were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 58 publications
7
26
1
Order By: Relevance
“…The purpose of this study is three-fold: (1) to record PTS and PTG of the general population due to COVID-19; (2) to explore the predictors of PTS and PTG, including the basic demographic information (e.g., sex and education), COVID-19 pandemic-related information (e.g., diagnosis and quarantine), psychological and physical reactions to COVID-19 (e.g., avoidance and insomnia), and on-the-spot mood (e.g., happy or sad on the testing day); (3) to examine the underlying relationship between PTS and PTG after the above predictors were controlled (i.e., hierarchical regression analyses). Referencing the previous publications, we predicted that being female (e.g., Liu et al, 2020 ), low-educated (e.g., L. Liang et al, 2020 ), quarantined (e.g., Wathelet et al., 2021 ), diagnosed with COVID-19 (e.g., Xiao et al, 2020 ), and clinical workers (e.g., Blekas et al, 2020 ), and having negative psychological or physical reactions to the pandemic (e.g., Yin et al, 2021 ) could all be stressors of PTS. More importantly, anticipating a ‘phoenix renascence’ ( Tamiolaki & Kalaitzaki, 2020 ), we propose a mutual positive prediction between the PTS and the PTG.…”
supporting
confidence: 56%
See 1 more Smart Citation
“…The purpose of this study is three-fold: (1) to record PTS and PTG of the general population due to COVID-19; (2) to explore the predictors of PTS and PTG, including the basic demographic information (e.g., sex and education), COVID-19 pandemic-related information (e.g., diagnosis and quarantine), psychological and physical reactions to COVID-19 (e.g., avoidance and insomnia), and on-the-spot mood (e.g., happy or sad on the testing day); (3) to examine the underlying relationship between PTS and PTG after the above predictors were controlled (i.e., hierarchical regression analyses). Referencing the previous publications, we predicted that being female (e.g., Liu et al, 2020 ), low-educated (e.g., L. Liang et al, 2020 ), quarantined (e.g., Wathelet et al., 2021 ), diagnosed with COVID-19 (e.g., Xiao et al, 2020 ), and clinical workers (e.g., Blekas et al, 2020 ), and having negative psychological or physical reactions to the pandemic (e.g., Yin et al, 2021 ) could all be stressors of PTS. More importantly, anticipating a ‘phoenix renascence’ ( Tamiolaki & Kalaitzaki, 2020 ), we propose a mutual positive prediction between the PTS and the PTG.…”
supporting
confidence: 56%
“…Second, whether the relationship between age and PTS is linear as for COVID-19 should be questioned. Third, it was found that perceived risk (e.g., feeling unsafe), negative mood (e.g., anxiety), adverse physical reactions (e.g., insomnia), as well as PTS were locked in a vicious circle for clinical workers combating COVID-19 ( Yin et al, 2021 ). However, whether this strong linkage can be generalized to the general population is indeterminate.…”
mentioning
confidence: 99%
“…Taken together, preexisting research studying the link between COVID-19 risk perception and sleep quality has focused solely on healthcare workers or medical staff [11,24]. This study was among the first to test the link between COVID-19 risk perception and sleep quality in the general population in Hong Kong, China.…”
Section: Introductionmentioning
confidence: 99%
“…The literature on risk perception suggests that risk perception consists of cognitive and affective components: The cognitive component refers to the perceived likelihood of oneself or others contracting the virus, whereas the affective component refers to experienced worries about developing disease [7,9]. However, only a handful of studies have examined the link between COVID-19 risk perception and sleep quality: to our knowledge, all the previous investigations focused on solely medical staff and healthcare workers [10,11]. For instance, Yin et al (2021) reported that medical staff who perceived higher risk of contracting COVID-19 at work also had poorer sleep quality [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation